Hydroponic gardening : the magic of modern hydroponics for the home gardener - Raymond Bridwell (London CRC Press, 2024)
This book explains the basic techniques of hydroponic gardening that help home gardener to do their gardening with a lot more relaxation and enjoyment and a much greater return of nutritious food, showing how to use simple automated systems to harvest fresh, abundant crops year-round.
Keywords: Food